Characterization of B-box family genes and their expression profiles under abiotic stresses in the Melilotus albus - Nian, Lili; Zhang, Xiaoning; Liu, Xingyu; Li, Xiaodan; Liu, Xuelu; Yang, Yingbo; Haider, Fasih Ullah; Zhu, Xiaolin; Ma, Biao; Mao, Zixuan; Xue, Zongyang (Frontiers in Plant Science, 2022)
B-box (BBX) proteins are one zinc-finger transcription factor that plays a critical role in plant development, growth, and multiple stress responses. Although BBX genes have been reported in many model organisms, no comprehensive study has yet been conducted on the BBX genes in Melilotus albus, and the biological functions of this family remain unknown. In this study, a total of 20 BBX (MaBBX) genes were identified in Melilotus albus and were phylogenetically divided into five clades. BBX members within the same clade showed similar domain organizations, suggesting similarity of biological function potentially. Distribution mapping shows that BBX proteins are nonrandomly localized in 8 chromosomes. Additionally, we found light-responsive, various hormone and stress-related cis-elements in the promoters of MaBBXs by analyzing cis-elements. Therefore, the expression levels of all MaBBXs were further detected under salt, cold (4◦C), and dark stresses in Melilotus albus. We found that 80% of the genes had higher expression levels after 3h of NaCl treatment, 10 genes were significantly upregulated after 3 h of lowtemperature treatment, and all genes were up-regulated after 3h of dark treatment, and then appeared to decline. Thus, these MaBBXs might be involved in the defense against abiotic stresses. Furthermore, the transient expression assay demonstrated that MaBBX15 was localized in the nucleus. This study provides useful information for further investigating and researching the regulatory mechanisms of BBX family genes in response to abiotic stresses in Melilotus albus.